Pan American first air mail flight: transatlantic "Northern Route" Port Washington-Foynes, June 24, 1939 - Pan American World Airways, Inc. (1939)
Includes crew list and photographs This item was digitized as part of the "Digitizing the 'World's Most Experienced Airline'" project, supported by a grant from the Council on Library and Information Resources (CLIR). The grant program is made possible by funding from The Andrew W. Mellon Foundation.